A new species of Strepsicrates Meyrick (Lepidoptera: Tortricidae) from the Atacama Desert of northern Chile previously misidentified as S. smithiana Walsingham - Vargas-Ortiz, Marcelo; Vargas, Héctor A. (Zootaxa, 2018)
The adult, larva, and pupa of Strepsicrates gattii Vargas-Ortiz & Vargas, sp. n. (Lepidoptera: Tortricidae: Olethreutinae: Eucosmini), are described and illustrated from the Atacama Desert of northern Chile. The larvae are leaf-tiers on the vulnerable native tree Morella pavonis (Myricaceae). As S. gattii was previously misidentified as S. smithiana Walsingham, morphological differences that enable the separation of the two species are highlighted. Sequences of the DNA barcode fragment of the cytochrome oxidase subunit I mitochondrial gene of the new species are provided and used in a Bayesian analysis with congeneric representatives to assess their relationships preliminarily. The divergence (K2P) with S. smithiana was 6.4–7.4%, providing additional support for separating the two species.